PROBLEMATIKA HILANGNYA HAK PILIH WARGA NEGARA YANG DITIMBULKAN PASAL 348 AYAT (9) UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILU DALAM MENGHADAPI PELAKSANAAN PEMILIHAN UMUM SERENTAK 2019 - Kusuma K., Ignasius Abdi; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
Writing this law is about the Problems of Loss of Citizens’ Voting Rights caused by Article 348 Paragraph (9) Act No. 7 Year 2017 concerning General Elections in the implementation of the 2019 Concurrent Election. The type of research that the author uses in compiling this legal research is normative legal research which is prescriptive and applicable. The aprroach that used is the statute approach. The sources of legal material used are primary legal material and secondary legal material. The legal material analysis technique used by the author is a law with a deduction method. Based on the results, the author assumed that Article 348 Paragraph (9) which require electronic KTP as an absolute requirement for voters to deliver their right to vote have caused problems for voters who do not have electronic ID cards. There is a Decision of the Constitutional Court No.20/PUU-XVII/2019 which states that the use of a certificate can be used as an alternative document to replace electronic KTP for those who do not have an electronic ID card.